Moyamoya disease associated with progressive systemic sclerosis A case report - Takenaka, Katsunobu; Deguchi, Kazuki; Niikawa, Shuji; Hattori, Tatsuaki; Ohkuma, Akio (Japanese Journal of Stroke, 1990)
A rare case of moyamoya disease associated with progressive systemic sclerosis (PSS) is reported. A 54-year-old housewife suddenly was suffered from severe headache and vomiting on June 8, 1987. On admission, CT scan revealed a subarachnoid hemorrhage without intracerebral or intravetricular hematoma. Cerebral angiogram showed an occlusion at the terminal portion of bilateral internal carotid arteries with moyamoya vessels. Conservative therapy was performed and resulted in relief of all symptoms except her chronic constipation. However, in winter, she gradually complained shibire feeling and pain in her fingers, followed by Raynaud's sign, discoloration of the nails and morning stiffness of her hand. Shortening and hypertrophy of her frenulum linguae, elongation of unguinal epithelium, edematous sclerosis of forearm skin, and pigmentation in lumbar region were also observed. Finger plethysmogram indicated the flattening of pulse wave after cold water loading. Histological finding of the forearm skin disclosed the atrophy of dermis and sweat gland, degeneration of adipose tissue surrounding the sweat gland, and narrow collagen fiber. These observations were compatible with the atrophic stage of PSS. However, serological examination showed autoimmune antibody was negative. Although the etiology of moyamoya disease has not been clarified until now, recent studies imply the systemic angitis through the action of autoimmune mechanism correlates the pathogenesis of moyamoya disease. This is the first report of association of moyamoya disease and PSS, suggesting the involvement of the immunological mechanism concerning the etiology of moyamoya disease.